(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters, where the first chapter included the definition of the research, i.e. the introduction, the importance of the research, the research problem, as well as the objectives, which are:- Preparing special educational units using cognitive strategies, which are two forms of mental stimulants according to compound exercises to learn some compound offensive skills in basketball.- To identify the effect of using two forms of mental stimulants according to compound exercises in learning some types of compound skills (knocking skill and shooting by jumping - slacking skill and peaceful shooting) in basketball.- Identifying which groups are better in learning some complex offensive skills in basketball (the skill of shooting by jumping and hitting - the skill of shooting peacefully and then hitting) in basketball.